Adaptabilitas Generasi Z dalam Menghadapi Era Disrupsi Digital Menuju Indonesia Emas 2045: Literatur Review - Nabila Puspita sari; Widiyatmo Ekoputro W (GLOBAL SCIENTS PUBLISHER, 2026)
This study employs a literature review approach to describe the adaptability of Generation Z in facing the era of digital disruption toward Indonesia Emas 2045. Transformations driven by the Industrial Revolution 4.0 and Society 5.0 have significantly impacted various sectors, particularly education, the economy, and the workplace. In this context, Generation Z, as digital natives, is expected to possess strong adaptive capabilities, including digital literacy, digital agility, and psychological resilience. The study was conducted by analyzing relevant scientific literature related to Generation Z and digital transformation. The findings indicate that Generation Z has considerable adaptability potential; however, they continue to face challenges such as skills gaps, limited digital literacy, and the need to strengthen adaptive competencies. Therefore, enhancing digital literacy, digital agility, and collaboration among educational institutions, the government, and industry is essential to prepare Generation Z for the challenges of digital disruption and to support the realization of Indonesia Emas 2045.